1970
DOI: 10.1136/jcp.23.1.81
|View full text |Cite
|
Sign up to set email alerts
|

A study of some of the methods of urinary collection in children

Abstract: SYNOPSIS Three methods of urine collection used currently in the diagnosis of urinary tract infection in children were studied. One hundred and fifty-two hospital patients were investigated: 92 by clean-catch method, 32 by the adhesive plastic bag technique, and 28 by suprapubic bladder aspiration. Results indicate that in the great majority of children a satisfactory diagnosis can be made on bacteriological grounds by the examination of specimens passed naturally and collected with care. In a minority of case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The starred data point was the first sample from a patient whose subsequent colony counts were > 10 7 cfu/ml. The technique used to collect the paired urine for each study is indicated at the bottom Meta-analysis 1: voided urines High-quality quantitative data for voided urines There were 13 valid papers [13,[20][21][22][23][24][25][26][27][28][29][30][31] including one with two sub-studies [23], giving 14 reports on 1270 children, of whom 106 had UTIs and 1164 did not (Table 1). Most groups studied children suspected of having UTIs, one collected a clean catch sample before catheterising children for micturating cystograms [31], one screened for UTIs in healthy school children [22], and two compared different voided collection techniques in healthy children in hospital [30] or at home [29].…”
Section: Analysis Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The starred data point was the first sample from a patient whose subsequent colony counts were > 10 7 cfu/ml. The technique used to collect the paired urine for each study is indicated at the bottom Meta-analysis 1: voided urines High-quality quantitative data for voided urines There were 13 valid papers [13,[20][21][22][23][24][25][26][27][28][29][30][31] including one with two sub-studies [23], giving 14 reports on 1270 children, of whom 106 had UTIs and 1164 did not (Table 1). Most groups studied children suspected of having UTIs, one collected a clean catch sample before catheterising children for micturating cystograms [31], one screened for UTIs in healthy school children [22], and two compared different voided collection techniques in healthy children in hospital [30] or at home [29].…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Twelve studies [13-17 25-28, 32, 33, 37] included 709 children, of whom 114 had UTIs and 595 did not (Table 1), but half of these only reported how many cases exceeded various pre-determined colony counts, leaving six that provided sufficient quantitative data for full analysis [13,[25][26][27][28]37]. Nearly half the subjects and two-thirds of those with UTIs were aged < 2 years.…”
Section: High-quality Quantitative Data For Spa Urinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Obtaining urine for microscopy and culture in children younger than 2 years is difficult as they are generally not toilet‐trained and will not void on demand. Different methods of urine collection include suprapubic aspiration (SPA), catheter specimen urine (CSU), clean‐catch urine (CCU) and bag specimen urine (BSU) . The American Academy of Paediatrics recommends obtaining urine by SPA or CSU, techniques which have lower contamination rates .…”
Section: Introductionmentioning
confidence: 99%
“…Different methods of urine collection include suprapubic aspiration (SPA), catheter specimen urine (CSU), clean-catch urine (CCU) and bag specimen urine (BSU). 7 The American Academy of Paediatrics recommends obtaining urine by SPA or CSU, techniques which have lower contamination rates. [8][9][10][11][12] The contamination rate for SPA and CSU ranges from 0 to 7% and 9 to 23%, respectively.…”
Section: Introductionmentioning
confidence: 99%